แนวทางในการบริหารนิติบุคคลอาคารชุด - ขำดี เมธา; พันธุ์พานิช นพดล (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: To study problems in and to provide guidelines for the management of condominium. METHODS: Gather information from in-depth interviews and group discussion with 25 key informants. RESULTS: Lack of knowledge of the Condominium Act and regular system checks. General administrative problems included the lack of knowledge and understanding of the operation and monitoring system. CONCLUSIONS: Develop condominium management in terms of the maintenance of the building system, monitoring the system that needs to be monitored continuously, and training for residents and management team as well as preparation of the condominium lay-out. General management should be selected and recruited from a quality management company with experience and expertise in accounting and finance.